Adenosine 5'-triphosphate sulphurylase from rice shoots: partial purification and properties - Mohamad, Aminuddin; Kooi, E. T. (Universiti Pertanian Malaysia, 1980)
ATP-sulphurplase was found in the soluble fraction of cell extracts ofrice shoots. The enzyme was purified 44-fold by ammonium sulphate fractionation, DEAE-cellulose and sephadex G-200 chrmatography. The optimum temperature ofthe enzyme is around 40°C while its pH optimum is between 7.5-8.5. Mg++ is required for its activity but group VI anions (molybdate, sulphate, selenate, tungstate), EDTA, HgH, azide, cyanide, sulphide and fluoride are inhibitory. The Km values for APS and pyrophosphate are 4.5 pM and 9.0 pM respectively.